Analysis of circular cylinder subsidence under creep conditions taking into account and not taking into account barrel distortion - Lokoshchenko, Alexander Mikhailovich; Mossakovsky, Pavel Alexandrovich; Teraud, Valentin Victorovich (Computational Continuum Mechanics, 2010)
The subsidence of a circular cylinder compressed between rigid stamps under steady-state creep conditions is investigated. We present two solutions, of which one is based on the assumption that all parameters of the stress-strain state of the cylinder are independent of the longitudinal coordinate, and the other suggests barrel distortion (this solution is constructed using the LS-DYNA software package). In both cases, the subsidence of the cylinder is studied for same size and time. Calculations of all principal parameters are performed for two loading regimes: the stamps approach one another at a constant speed, and the applied compression force is constant. It is shown that the compression energy in the first variant is less than in the second variant (difference in the subsidence for specified processes is equal to 8-10%). The subsidence of the cylinder for fixed size and time under the assumption of barrel distortion requires less energy than in the case when the shape of the cylinder remains unchanged.
Keywords: circular cylinder; subsidence; creep; friction; barrel distortion; energy approach; LS-DYNA software package